Diversifikasi Pengolahan Jagung Ketan Merah (Zea mays ceratina) Menjadi Yogurt dengan Fortifikasi Susu Skim dan Sukrosa - Railia Karneta (Seminar Nasional Lahan Suboptimal, 2019)
Karneta R.  2019. Processing diversification of red glutinous corn (Zea mays ceratina) become yogurt with skim milk and sucrose fortification. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal 2019, Palembang 4-5 September 2019. pp. 409-417. Palembang: Unsri Press. Red glutinous corn is one of type corn which has levels high amylopectin and anthocyanin pigments. To increase the economic value of this corn processing diversification into yogurt. Con yogurt is a processed product of corn milk which is fermented using Lactobacillus bulgaricus and Streptococccus thermophillus. This study aims to determine the characteristics of red glutinous corn yogurt with sucrose and skim milk fortification. The experiment used a factorial completely randomized design. The first factor was sucrose fortification with a level of 0%, 2.5%, 5%, and 7.5%, and the second factor is skim milk wth a level 3%, 4%, and 5%. Experiment with three replications. The results showed thad sucrose, skim milk fortification and its interactions showed a very significant effect on protein levels, lactic acid levels, pH, and total acis. Red glutinous corn yogurt with sucrose and skim milk fortification meets yogurt standards with a protein content of more than 2.7%, lactic acid content of 0.8%. Organoleptic test resulkts that panelists liked red glutinous corn yogurt with 7.5% sucrose and 5% skim milk fortification.Keywords: red glutinous corn, sucrose, skim milk, yogurt